2018
DOI: 10.1002/chem.201802048
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of 3D Symmetric Flowerlike Sb2S3 Nanostructures in Dye‐Sensitized Solar Cells

Abstract: Antimony sulfide (Sb S ) is an important chalcogenide belonging to Group V-VI that is suitable for application as a photoelectric material in the fields of photocatalysis, photoconductive detectors, ion conductor materials, and solar energy conversion materials. Herein, a facile, one-step hydrothermal method is used to synthesize a 3D, symmetric, flowerlike Sb S nanostructure. The structure was composed of numerous nanoneedles, which provided a large void fraction and specific surface area. Characteristic meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The XRD and EDS of prepared samples were presented in Figure S1 and Figures S2 – S7 . XRD pattern of samples S 1 –S 6 in Figure S1 showed that S 3 had an amorphous structure, while other samples crystallized as orthorhombic SbSI and orthorhombic Sb 2 S 3 closely matched well with the previous reports on the XRD pattern of SbSI nanostructures 39 42 . EDS results for the qualitative analysis of SbSI/Sb 2 S 3 nanocomposites were presented in Figures S2 – S7 and approved the presence of elements S, Sb, and I in prepared samples which could be assigned SbSI/Sb 2 S 3 nanocomposites.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The XRD and EDS of prepared samples were presented in Figure S1 and Figures S2 – S7 . XRD pattern of samples S 1 –S 6 in Figure S1 showed that S 3 had an amorphous structure, while other samples crystallized as orthorhombic SbSI and orthorhombic Sb 2 S 3 closely matched well with the previous reports on the XRD pattern of SbSI nanostructures 39 42 . EDS results for the qualitative analysis of SbSI/Sb 2 S 3 nanocomposites were presented in Figures S2 – S7 and approved the presence of elements S, Sb, and I in prepared samples which could be assigned SbSI/Sb 2 S 3 nanocomposites.…”
Section: Resultssupporting
confidence: 89%
“…Based on the results, degradation efficiency was decreased by more than 30% by increasing the temperature of shaking from 20 to 70 °C. This happens because we were close to the curie temperature by increasing the temperature and the catalyst will show a more symmetric structure 41 , 42 .…”
Section: Resultsmentioning
confidence: 97%
“…The two pairs of redox peaks on the CV curves have similar shapes as the Pt CE suggesting that the AuSe CEs have similar catalytic activity during the redox process. 17,25 The negative (left side) and positive (right side) are represented by eqn (1) and (2), respectively. 26,27 I 3 − + 2e − ↔ 3I − 3I 2 + 2e − ↔ 3I 3 − …”
Section: Resultsmentioning
confidence: 99%
“…14,15 Variations such as different carbonaceous materials, carbon-metal composites, polymers and inorganic materials such as metal chalcogenides and metal oxides have been explored as replacement CEs for platinum. 1,8,[16][17][18] In addition to the properties listed above, a high surface area is an added advantage for a counter electrode as it allows for faster catalytic redox activity. Transition metal chalcogenides with a two-dimensional layered structure have this feature and have therefore drawn much attention as potential alternative CEs in DSSCs.…”
Section: Introductionmentioning
confidence: 99%